Association between media exposure and behavioral problems among preschool children - Zoromba, Mohamed A.; Abdelgawad, Doaa; Hashem, Sahar; El-Gazar, Heba; Abd El Aziz, Magda Ahmed (Frontiers in Psychology, 2023)
Background The prevalence of behavioral problems among preschool children is remarkably increasing in the clinical setting. Aim The current study aimed to investigate the association between media exposure and behavioral problems among preschool children. Methods This survey study recruited 560 children from 10 nurseries selected randomly, located in El-Mansoura, Egypt. Tools included socio-demographic characteristics the Media Exposure Questionnaire and the Conners Comprehensive Behavior Rating Scales (CBRS-48). Results The participants were exposed to media for an average of 105.84 min per day and displayed moderate levels in all subscales of CBRS-48. The duration of media exposure was significantly correlated to the hyperactivity index, learning problems, hyperactivity/impulsivity, conduct problem, anxiety, and psychosomatic problems (r = 0.372, 0.356, 0.323, 0.306, 0.298, 0.291, and 0.255, respectively). Conclusion The duration of media exposure was significantly correlated to the subscales of CBRS-48. Implication for nursing practice Preschool children should be engaged in concrete activities and social interactions that may lessen negative media effects such as hyperactivity, learning problems, hyperactivity/impulsivity, conduct problem, anxiety, and psychosomatic problems.